PENGEMBANGAN BAHAN AJAR STRUKTUR ALJABAR BERBASIS WEBSITE - Fadli Fadli (Perspektif Ilmu Pendidikan, 2011)
This research was conducted to produce a web based learning materials which is used in algebra structure course. The respondents of this research were student teachers of 6th semester, majoring in Maths, Faculty of Educational and Teaching Program, University of PGRI Palembang. The learning materials were developed by IDI (Instructional Development Institute) model. To measure of its validity, practicality, and effectiveness, a formative evaluation and a field test were used. The results showed that the 4th prototype of the learning materials is potentially effective that 67,57% of students are motivated, 56,76% of students are interested and the studentsâ€™ result of study which reached the point of 54,05%, are considered excellent. It can be concluded that the learning materials of structure of algebra based on website is valid and practical on study of structure of algebra, and has a potential effect.